Briefing: Continuous monitoring and adaptive control: the 'smart' storm water management solution. Issue 4 (3rd April 2018) - Wright, Jeffrey; Marchese, Dayton
Abstract : The approach to managing storm water, and the implementation of storm water infrastructure, has not kept pace with the digitally enabled environment. Since the first run-off systems designed in ancient times, moving storm water away from cities to protect life and property has been the primary concern – out of sight, out of mind. The engineering and science community agree: extreme weather events and climatic conditions such as floods and droughts are more likely in the future. To keep up, the built environment is changing by integrating smart technologies and holistic approaches to infrastructure design and management. Regulations for the mitigation of pollution caused by urban run-off require more accuracy than those in the past. Future water resources design must adapt to these new conditions. Adaptation includes using smart systems, such as continuous monitoring and adaptive control, to repurpose the existing infrastructure and build modern systems that harness storm water's latent value – changing what was once thought of as a liability into an asset.